The Promise and Future of Neo‐Functional Peace: A Reply to Bergmann and Niemann. (9th November 2017) - Visoka, Gëzim; Doyle, John
Abstract: Julian Bergmann and Arne Niemann claim that 'neo‐functional peace' was insufficiently conceptualized and empirically unsubstantiated. They draw on the original neo‐functionalist literature to propose a logic of spillover to explain the European Union's external policies. We argue that our original article is not damaged by this critique and its explanation of the EU's approach in the Serbia‐Kosovo case stands. We accept the need for further work, based on analysis of different examples and sectors, which can clarify the conceptual boundaries of neo‐functional peace and test it against other cases.